Empagliflozin Effectively Attenuates Olanzapine-Induced Body Weight Gain in Female Wistar Rats - Ashraf, Ghulam Md; Alghamdi, Badrah S.; Alshehri, Fahad S.; Alam, Mohammad Zubair; Tayeb, Haythum O.; Tarazi, Frank I. (Frontiers in Pharmacology, 2021)
Atypical antipsychotic drugs are commonly associated with undesirable side effects including body weight gain (BWG) and metabolic deficits. Many pharmacological interventions have been tested in an attempt to minimize or prevent these side effects. Preliminary evidence suggests that antidiabetic drugs may be effective in attenuating antipsychotic-induced BWG. In the current study, we examined the effect of an antidiabetic drug empagliflozin (EMPA) on BWG induced by anatypical antipsychotic drug olanzapine (Ola) in female and male Wistar rats. Rats were divided into six groups based on the dose they received: group 1 (female control), group 2 (female EMPA, 20 mg/kg; IG), group 3 (female Ola, 4 mg/kg; IP), group 4 (female Ola, 4 mg/kg; IP + EMPA, 20 mg/kg; IG), group 5 (male control), and group 6 (male Ola, 4 mg/kg; IP). Ola induced sustained increase in BWG. The subsequent treatment of Group 3 and 4 with EMPA attenuated the Ola-induced BWG in female Wistar rats. In terms of the gender difference between female and male Wistar rats, the male control group 5 gained more weight throughout the study as compared to the female control group 1. Similarly, the male Ola group 6 gained more weight throughout the study as compared to the female Ola group 3. However, Ola did not cause any weight difference between male rats treated with Ola in comparison with male control group, thus showing a significant gender difference regarding body weight between male and female Wistar rats regardless of Ola administration. In addition, the present findings showed that EMPA effectively attenuates the Ola induced BWG in female Wistar rats. These novel findings should help to better understand the underlying molecular and behavioral mechanisms contributing to the observed increase in body weight after treatment with Ola and other atypical antipsychotic drugs across male and female rats.